Agency and Autonomy in the Maritime Silk Road Initiative: An Examination of Djibouti's Doraleh Container Terminal Disputes. (2nd August 2021) - Barton, Benjamin
Abstract: Touted as the second coming of the Hambantota debt-for-equity swap deal, the ongoing legal dispute pitting Dubai Ports (DP) World (United Arab Emirates) and China Merchants Port (CMP) over the Doraleh Container Terminal (DCT) (Djibouti) in front of the Hong Kong High Courts has been hastily interpreted as yet another act of Chinese economic statecraft. Yet, when looking more closely at the specifics of this dispute, it would appear that the evidence does not lend itself favourably to those who advocate the power of Chinese political leverage in return for "debt traps". This article debunks the myth of Chinese grand strategy as the driving force behind the legal dispute over the DCT, by instead placing the combination of Djiboutian elite agency and CMP's entrepreneurial autonomy as the primary causal variables. It does so by predominantly drawing on unexplored publicly available data obtained from the various legal disputes pertaining to the DCT.